Potensi Produksi Kacang Tanah Lokal Situraja - Try Zulchi (Universitas Muhammadiyah Yogyakarta, 2016)
In Sumedang, local variety of groundnut DM Situraja has a great potential and showed increasing production rates. This support the agribusiness development of groundnut in Sumedang District and surrounding areas. The objective of this experiment was to determine production potential of local variety groundnut Situraja especially in Sumedang. This research was arranged in a randomized complete block design whereas each treatment was replicated 4 times. The data were analyzed using SPSS version 16 and treatment means were separated using LSD (Least Significant Difference) with 5% error level. The results indicated that morphology of Situraja variety had an upright growth habit, rod-shaped and green purplefish, 2-seeded, and seed weight 40-55 g for 100 seeds, maturing age of 90 days, and the production potential 3,02 t/ha. The content of oil was 45%, with a relatively high protein content of 28% and crunchy sweet taste. High productivity of DM Situraja local variety was resulted by interaction between variety and spesific enviroment.